PENGEMBANGAN KARAKTER KEPEDULIAN MELALUI KURIKULUM “SENTRA” DENGAN MENGGUNAKAN MODEL ADDIE - Fauzi, Ahmad; Winata, Widia; Ansharullah, Ansharullah (Instruksional, 2020)
The writing of this article is motivated by the existence of a narrow view of human intelligence, the reality is that smart children are children whose mathematical value or language is high while children who have good character, have a high awareness of the surrounding environment are considered not intelligent and at finally, intelligent human resources emerged, but they lacked the nature of care, so the writer was moved to examine whether the nature of caring could be developed through teaching and learning activities in this case through the central approach using the ADDIE model. The method used is by using the Research and Development (R & D) method with a qualitative approach and the ADDIE model. The results of the study show that the nature of caring can be developed through learning strategies outlined through learning implementation plans (RPP). This is evidenced by the authors making observations, interviews and field notes and merging learning activities at SDIT Permata Madani by recording each incident, which in the end through design development of the nature of student care can increase awareness of the environment, teachers, peers, things and school in general.